New Detection Modules for Free Space Optics - Gutowska, Magdalena; Gawron, Waldemar; Nowakowski, Mirosław; Bielecki, Zbigniew; Mikołajczyk, Janusz; Szabra, Dariusz (Photonics Letters of Poland, 2010)
The paper presents the construction and test results of new detection modules for Free Space Optical Data Link operated in the 8-12 um wavelength range. In these modules Polish detectors manufactured at the Polish VIGO System Ltd. company were applied. High sensitivity of the detection modules was achieved using photodiodes with immersion lens. Detector noise was reduced as a result of photodiode cooling by means of a four-stage thermoelectric cooler and reverse biasing. The developed detection modules will be used in a next-generation optical link capable of operating in more difficult weather conditions as compared to the links currently offered. Two detection modules were tested. The first of them consists of a photodiode without biasing, and the second one of a photodiode with reverse biasing Full Text: PDF References H. Manor, A. Argon,"Performance of an Optical Wireless Communication System as a Function of Wavelength", Appl. Opt. 42(21), 1 (2003)[CrossRef] J.C. Juarez et al.,"Free-Space Optical Communications for Next-generation Military Networks", IEEE Comm. Magaz. 44, 46 (2006)[CrossRef] K. Kinkade,"Free-space-Optics builds invisible bridges", Laser Focus World 39(12), 69 (2003) M. Achour, Free space optics builds invisible selection: 10µm versus shorter wavelengths, http://www.ulmtech.com Z. Bielecki, M. Brudnowski, W. Gawron, J. Pawluczyk, A. Piotrowski, J. Piotrowski,"Integrated IR detector packages for the second generation of free-space optical links", Electronika 7-8, 95 (2008) A. Rogalski, Z. Bielecki, Detection of optical radiation in Handbook of optoelectronics, vol. 1 (Taylor & Francis, London 2006) P. Norton, "HgCdTe infrared detectors", Opto-electron. Rev. 10(3), 159 (2002)http://www.wat.edu.pl/review/optor/10(3)159.pdf D. Stanaszek, J. Piotrowski, A. Piotrowski, W. Gawron, Z. Orman, R. Paliwoda, M. Brudnowski, J. Pawluczyk and M. Pedzińska,"Mid and long infrared detection modules for picosecond range measurements", Proc. SPIE 7482, 74820M (2009)[CrossRef] A. Piotrowski, J. Piotrowski, W. Gawron, J. Pawluczyk, and M. Pedzinska,"Extension of Usable Spectral Range of Peltier Cooled Photodetectors", Acta Physica Polonica A 116, 52 (2009) J. Rutkowski,"Planar junction formation in HgCdTe infrared detectors", Opto-electron. Rev. 12(1), 123 (2004) Z. Bielecki,"Maximisation of signal-to-noise ratio in infrared radiation receivers", Opto-electron. Rev. 10(3), 209 (2002) Z. Bielecki,"Readout electronics for optical detectors", Opto-electron. Rev. 12(1), 129 (2004) A. Piotrowski, J. Piotrowski, W. Gawron, J. Pawluczyk, M. Pedzinska,"Extension of Usable Spectral Range of Peltier Cooled Photodetectors", Acta Physica Polonica A 116, 52 (2009) J. Piotrowski, J. Pawluczyk, A. Piotrowski, W. Gawron, M. Romanis, and K. Kłos,"Uncooled MWIR and LWIR photodetectors in Poland", Opto-Electron. Rev. 18(3), 24 (2010)[CrossRef] Z. Bielecki, A. Rogalski, Detection of Optical Signals (WNT, Warsaw 2001)